b - Darwin, Charles (b, 2001)
Darwin's famous account of his five-year expedition around the world, as a naturalist on board HMS Beagle, and the observations he made, especially in the coastal areas of South America, that eventually led to his theory of natural selection.
Keywords: Voyages around the world -- History -- 19th century